1996
DOI: 10.1099/0022-1317-77-7-1537
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein H of human cytomegalovirus is a major antigen for the neutralizing humoral immune response

Abstract: A recombinant baculovirus expressing glycoprotein H (gpUL75) of human cytomegalovirus was used to examine the humoral immune response in naturally infected individuals. Recombinant baculovirus infected insect cells produced two forms of gH with molecular masses of 78-82 kDa and 94 kDa. The 94 kDa polypeptide was modified by high mannose oligosaccharide side-chains as shown by reduction in molecular mass after treatment with endoglycosidases H and F. The 78-82 kDa protein represented the non-glycosylated precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 45 publications
1
65
0
Order By: Relevance
“…Protein alignment of CMV strain VR1814 to 10 CMV strains isolated from geographically distinct regions demonstrated diversity in all of the CMV glycoproteins, including the UL128, UL130, and UL131a proteins, with the greatest diversity appearing in gN and gO (Table 3). The natural humoral immune response to CMV primarily induces antibodies directed against gB; however, antibodies targeting gM/gN and gH/gL have also been identified (109,134,135). Recent work also revealed the exquisite potency of human-derived monoclonal antibodies (MAbs) that target the PC in blocking infection of epithelial, endothelial, and monocytic cells (111,136,137).…”
Section: Strain Polymorphism Contributes To Immune Evasionmentioning
confidence: 99%
“…Protein alignment of CMV strain VR1814 to 10 CMV strains isolated from geographically distinct regions demonstrated diversity in all of the CMV glycoproteins, including the UL128, UL130, and UL131a proteins, with the greatest diversity appearing in gN and gO (Table 3). The natural humoral immune response to CMV primarily induces antibodies directed against gB; however, antibodies targeting gM/gN and gH/gL have also been identified (109,134,135). Recent work also revealed the exquisite potency of human-derived monoclonal antibodies (MAbs) that target the PC in blocking infection of epithelial, endothelial, and monocytic cells (111,136,137).…”
Section: Strain Polymorphism Contributes To Immune Evasionmentioning
confidence: 99%
“…By contrast, coexpression of gB, gH, and gL triggers syncytium formation due to cell-cell fusion (E. R. Kinzler and T. Compton, submitted for publication). Both gB and gH are highly antigenic in CMV-infected individuals, and many antibodies directed against these two glycoproteins are neutralizing to CMV, blocking infection at the level of entry (3,9,27,31). To date, molecular details underlying the mechanism of CMV entry into host cells remain elusive.…”
mentioning
confidence: 99%
“…Although the immunologic responses against several of the major HCMV surface glycoproteins, including glycoprotein B (gB) and gH, have been extensively characterized, only limited studies of the responses to the gM/gN complex have been reported (13,18,(30)(31)(32)(41)(42)(43). The gM/gN complex is the most abundant glycoprotein component of the HCMV virion envelope (44).…”
mentioning
confidence: 99%